Effect of Armed Conflict on Intimate Partner Violence : Evidence from the Boko Haram Insurgency in Nigeria - Ekhator-Mobayode, Uche Eseosa; Hanmer, Lucia C.; Rubiano Matulevich, Eliana Carolina; Arango, Diana Jimena (World Bank, Washington, DC, 2020)
Intimate partner violence is the most common form of violence against women in conflict and non-conflict settings, but in conflict settings it often receives less attention than other forms of gender-based violence, such as conflict-related sexual violence. Using data from the 2008 and 2013 Domestic Violence module of the Nigerian Demographic and Health Survey spatially linked to the Boko Haram actor file of the Armed Conflict Location and Events Database, this paper employs a kernel-based difference-in-difference model to examine the effect of the Boko Haram insurgency on women's experience of physical and sexual intimate partner violence. It also examines the effect of the Boko Haram insurgency on women's experience of controlling behavior from a husband or partner, women's autonomy in household decision making, and their control over their own earnings. The paper finds that the Boko Haram insurgency is associated with slower progress toward preventing and eliminating women's experiences of physical and sexual intimate partner violence. Controlling behaviors from husbands/partners and reductions in women's autonomy in household decision making are heightened in locations that are impacted by the Boko Haram insurgency, indicating that the Boko Haram insurgency adversely affects women's agency and exacerbates behaviors that are often precursors to intimate partner violence.